2014
DOI: 10.1002/2013gb004794
|View full text |Cite
|
Sign up to set email alerts
|

Western Pacific atmospheric nutrient deposition fluxes, their impact on surface ocean productivity

Abstract: The atmospheric deposition of both macronutrients and micronutrients plays an important role in driving primary productivity, particularly in the low-latitude ocean. We report aerosol major ion measurements for five ship-based sampling campaigns in the western Pacific from~25°N to 20°S and compare the results with those from Atlantic meridional transects (~50°N to 50°S) with aerosols collected and analyzed in the same laboratory, allowing full incomparability. We discuss sources of the main nutrient species (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 95 publications
(230 reference statements)
2
54
1
Order By: Relevance
“…The model estimates here consider mainly the effects of nitrogen deposition on nitrogen fixation. However, there is increasing evidence that atmospheric iron deposition also plays a key role in nitrogen fixation because of the high iron requirements of nitrogen‐fixing enzymes [ Ito et al ., ; Martino et al ., ; Moore et al ., ; Ward et al ., ]. The dominance of nitrogen fixation we identify here, and the uncertainty in its sensitivity to atmospheric nitrogen and iron inputs and water column phosphorus cycling [ Landolfi et al ., ], suggests that the magnitudes and controls on nitrogen fixation merit further research.…”
Section: Impacts Of Atmospheric Deposition On Water Column Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The model estimates here consider mainly the effects of nitrogen deposition on nitrogen fixation. However, there is increasing evidence that atmospheric iron deposition also plays a key role in nitrogen fixation because of the high iron requirements of nitrogen‐fixing enzymes [ Ito et al ., ; Martino et al ., ; Moore et al ., ; Ward et al ., ]. The dominance of nitrogen fixation we identify here, and the uncertainty in its sensitivity to atmospheric nitrogen and iron inputs and water column phosphorus cycling [ Landolfi et al ., ], suggests that the magnitudes and controls on nitrogen fixation merit further research.…”
Section: Impacts Of Atmospheric Deposition On Water Column Productivitymentioning
confidence: 99%
“…This estimation of an important recycled marine component of DON is consistent with estimates from observational studies on Bermuda [ Altieri et al ., ], although at other locations anthropogenic terrestrial sources have been argued to dominate the DON [ Jickells et al ., ]. The DON model results reported here estimate gross DON deposition at 15–20% of total N deposition (Figure ) which is broadly in line with recent measurements of the proportion of DON in aerosols and rainwater over the Atlantic, 7–10% [ Zamora et al ., ], ~24% [ Lesworth et al ., ], and 19% [ Altieri et al ., ], and Pacific, 16% [ Martino et al ., ]. However, the proportion varies greatly regionally from 4 to 62% [ Zamora et al ., ].…”
Section: Atmospheric Depositionmentioning
confidence: 99%
“…S6 also shows the comparison of the annual cycles of the atmospheric concentrations (TP and PO 4 ) and deposition fluxes (dry and wet deposition), against the TM4-ECPL monthly model results. For cruise measurements over the Atlantic and Pacific oceans (Baker et al, 2010;Martino et al, 2014;Powell et al, 2015) and the global compilation of deposition rates (Vet et al, 2014), the observations are also spatially averaged inside the same model grid box. These comparisons show almost similar performance for all sensitivity simulations but with one falling, in most cases, close to the lower edge of observed concentrations and deposition fluxes.…”
Section: Evaluation Of Phosphorus Simulationsmentioning
confidence: 99%
“…Falkowski et al, 1998;Mills et al, 2004;Jickels et al, 2005 and refs. therein;Martino et al, 2014). In the tropical North Atlantic where phytoplankton communities are nitrogen limited, experiments conducted by Mills et al (2004) have shown Saharan dust addition to stimulate nitrogen fixation in this area, presumably by supplying iron and phosphorous.…”
Section: Influence Of Saharan Dust Depositionmentioning
confidence: 99%